Perception on prevention of mother-to-child-transmission (PMTCT) of HIV among women of reproductive age group in Osogbo, Southwestern Nigeria - Olugbenga-Bello, AI (Dove Medical Press, 2013)
INTRODUCTION: The fastest growing group of adults living with human immunodeficiency virus (HIV), is women. As more women contract the virus, the number of children infected in utero, intra-partum, and during breastfeeding has been growing. This study assessed the knowledge and attitude of women of child bearing age towards the prevention of mother-to-child-transmission (PMTCT) of HIV. MATERIALS AND METHODS: This is a descriptive cross sectional survey of 420 women of the reproductive age group (15–49 years) selected using a multistage sampling technique. Data were obtained using interviewer-administered, pretested, semistructured questionnaires. The data were analyzed using the Statistical Package for Social Sciences (SPSS) software version 15. RESULTS: A high level of awareness about HIV/acquired immunodeficiency syndrome (AIDS) was observed among the respondents (99.8%). The knowledge about MTCT and PMTCT of HIV was high, 92.1% and 91.4%, respectively. However, a significant portion (71.27%) of the study population had poor attitudes towards PMTCT of HIV. CONCLUSION: Despite the high level of awareness of HIV/AIDS, and good knowledge about MTCT and PMTCT of HIV/AIDS among the respondents, the attitude towards PMTCT is poor. There is need for the involvement of the stakeholders in bridging the gap between knowledge and attitude of prevention of MTCT of HIV among women.